Compact folded square‐loop antenna for reading near‐field RFID tags in blood sample tracking system. Issue 25 (1st December 2017) - Lin, Y.F.; Liao, C.T.; Chen, H.M.; Jiang, Z.D.
Abstract : A highly compact (25 × 25 × 0.8 mm 3 ) dual‐band folded square‐loop antenna is proposed for reading near‐field RF identification (RFID) tags. The antenna has a strong and uniform magnetic field in the near‐field zone of the square loop. The side length of the square loop (∼ λ /16) generates resonant frequencies in two conventional modes (0.5 λ and 1.0 λ ). Experimental interrogation of a small RFID button tag attached to a blood sample collection tube showed that the antenna has a small interrogation zone (15 × 15 mm 2 ), which avoids unnecessary interrogation. Experiments also showed that with an input power of 25 dBm, the antenna can tag at a distance of up to 40 mm, which confirmed its suitability for reading button‐type RFID tags attached to blood sample collection tubes and other specimen containers.